Adsorptive removal of crude petroleum oil from water using floating pinewood biochar decorated with coconut oil-derived fatty acids - Gurav, Ranjit; Bhatia, Shashi Kant; Choi, Tae Rim; Choi, Yong Keun; Kim, Hyun Joong; Song, Hun Suk; Park, Sol Lee; Lee, Hye Soo; Lee, Sun Mi; Choi, Kwon Young; Yang, Yung Hun (Science of the Total Environment, 2021)
The present investigation deals with the adsorptive removal of crude petroleum oil from the water surface using coconut oil-modified pinewood biochar. Biochar generated at higher pyrolysis temperature (700 °C) revealed higher fatty acid-binding efficiency responsible for the excellent hydrophobicity of the biochar. Fatty acids composition attached to the biochar produced at 700 °C was (mg g−1 BC) lauric acid (9.024), myristic acid (5.065), palmitic acid (2.769), capric acid (1.639), oleic acid (1.362), stearic acid (1.114), and linoleic acid (0.130). Simulation of the experimental adsorption data of pristine and modified pinewood biochar generated at 700 °C offered the best fit to pseudo-first-order kinetics (R2 > 0.97) and Langmuir isotherm model (R2 > 0.99) based on the highest regression coefficients. Consequently, the adsorption process was mainly driven by surface hydrophobic interactions including π-π electron-donor-acceptor between electron-rich (π-donor) polycyclic aromatic hydrocarbons from the crude oil and biochar (π-acceptor). A maximum adsorption capacity (Qmax) of 5.315 g g−1 was achieved by modified floating biochar within 60 min. Whereas the reusability testing revealed 49.39% and 51.40% was the adsorption efficiency of pristine and modified biochar at the fifth adsorption-desorption cycle.
Keywords: Adsorptive removal; Bio chars; Coconut oil; Fatty acid modified adsorbent; Petroleum oil; Petroleum oil spill; Pinewood pyrolyse; Pruning waste biomass; Pyrolysis temperature; Water surface; Adsorption; Charcoal; Coconut Oil; Fatty Acids; Kinetics; Lauric Acids; Petroleum; Pinus; Water; Water Pollutants, Chemical; Fatty acid modified adsorbent; Petroleum oil spill; Pinewood pyrolysis; Pruning waste biomass